Manufacture of Incident Management Procedures for Handling Complaints on PPTI based Framework ITIL V-3 - Rizkillah, Taskhiyatul Nufus; Sutomo, Erwin; Maulana, Yoppy Mirza (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2016)
Complaints handling services in a part of Penerapan dan Pengembangan Teknologi Informasi (PPTI) having a process handling incident performed only according the estimated, knowledge, and experience developers network or application. Recording the activities carried out when handle incident also only done by the staff who handle, so there was not history of the incident on the part PPTI. For that need to create procedure incident management that integrated with refer to Framework Information Technology Infrastructure Library (ITIL) V-3. ITIL V-3 is a series of concepts and techniques infrastructure management, development, and information technology operations (TI) which focused on operational service and can give recommendation for the company about how to handle the incident and exactly used as benchmark for arrange the work structured to provide services company. The creation of this procedure incident management will produce standards consist of standars, procedures, and forms used incident management in Service Operation – ITIL V-3. The results of these research is produces 9 standars, 14 procedures, and 17 forms.